Drainage of Giant Liver Abscess by Robotic Surgery: Case Report - Gaytán-Fuentes, Omar Felipe; Flores-Lopez, Alejandro Alberto; Guerrero-Ortega, Noely Xochitl Leonor; Romero-Macías, Arturo; Cerón-Castillo, Ricardo; Barajas-Galicia, Edith; Barba-Mendoza, Jairo Arturo; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: The robot-assisted surgery system has overcome some technical bottlenecks of laparoscopy and dramatically improves the flexibility and precision of liver operation. It can also provide the magnified field of surgery and the three-dimensional view, facilitating intracorporeal sutures and visualization of delicate tissue anatomy. However, several limitations, such as the robot's high cost and high failure rate, prevent its popularization. Clinical Case: She has admitted a 54-year-old female via the emergency room due to abdominal pain and a liver cyst. He began two weeks prior to admission with intense pain located in the right hypochondrium irradiating towards the contralateral hypochondrium; he went to a private doctor who told him to perform a UDG of the abdomen in which the presence of a liver cyst, which is why go to this hospital. An abdominal tomography was performed, which reported: an ovoid, hypodense image with slightly lobed and well-defined edges, which measures 8.7 x 16.4 x 9.9 cm in its principal axes with an approximate volume of 738 mL and located in segments VI, VII, and VIII; It presents a wall with a thickness of up to 14 mm, which presents moderate and heterogeneous enhancement after the passage of the contrast medium; dilatation of the intrahepatic bile duct up to 7.6 mm. Discussion: Robotic surgery is superior to conventional laparoscopic surgery in various complex surgical procedures. For example, in radical prostatectomy, the robotic approach has been associated with an earlier return of sexual function compared with conventional laparoscopic surgery, attributed to a more remarkable ability to preserve the cavernous nerve. Conclusion: Drainage of a giant liver abscess has not been reported to date resolved by robotic surgery.